Prolific.ac—A subject pool for online experiments - Palan, Stefan; Schitter, Christian (Journal of behavioral and experimental finance, 2018)
The number of online experiments conducted with subjects recruited via online platforms has grown considerably in the recent past. While one commercial crowdworking platform – Amazon’s Mechanical Turk – basically has established and since dominated this field, new alternatives offer services explicitly targeted at researchers. In this article, we present www.prolific.ac and lay out its suitability for recruiting subjects for social and economic science experiments. After briefly discussing key advantages and challenges of online experiments relative to lab experiments, we trace the platform’s historical development, present its features, and contrast them with requirements for different types of social and economic experiments.